Management of Pruritus in Chronic Liver Disease - Angeline Bhalerao; Gurdeep S. Mannu (Hindawi Limited, 2015)
Background. There continues to be uncertainty on the ideal treatment of pruritus in chronic liver disease. The aim of this study was to gather the latest information on the evidence-based management of pruritus in chronic liver disease. Methodology. A literature search for pruritus in chronic liver disease was conducted using Pubmed and Embase database systems using the MeSH terms "pruritus," "chronic liver disease," "cholestatic liver disease," and "treatment." Results. The current understanding of the pathophysiology of pruritus is described in addition to detailing research into contemporary treatment options of the condition. These medical treatments range from bile salts, rifampicin, and opioid receptor antagonists to antihistamines. Conclusion. The burden of pruritus in liver disease patients persists and, although it is a common symptom, it can be difficult to manage. In recent years there has been greater study into the etiology and treatment of the condition. Nonetheless, pruritus remains poorly understood and many patients continue to suffer, reiterating the need for further research to improve our understanding of the etiology and treatment for the condition.